Evaluation of toll-like receptors (TLRs) gene expression in feline infectious peritonitis virus (FIPV)-infected cell line - Nur Atiqah binti Muhammad Ali. (2017)
Feline infectious peritonitis (FIP) is one of the most infectious fatal diseases involving immune-mediated events caused by feline infectious peritonitis virus (FIPV), a highly virulent biotype of feline coronavirus. There are limited studies characterizing the innate immune component of FIP. Toll-like receptors (TLRs) recognition is one of the mechanisms used in innate immunity to detect repeated molecular pattern of pathogens. Thus, this study was conducted to evaluate the modulation of TLR3 and TLR7 genes expression in FIPV-infected cell line. Crandell-Reese Feline Kidney (CRFK) cell line was infected with FIPV 79-1146 at MOI = 0.01 and the expression of TLR3 and TLR7 were measured using Real-Time Polymerase Chain Reaction (qPCR) at different time points (3 and 24 hours post-infection (hpi). For both TLR3 and TLR7 genes, the expression was upregulated at 3 and 24 hpi when compared with control. In addition, there was a 5-fold significant increase of TLR3 gene expression at 24 hpi compared to 3 hpi. The viral load at the different time points was not measured; however, the infectivity of the virus was confirmed using conventional RT-PCR assay. In conclusion, it appears that both TLR3 and TLR7 were upregulated in FIPV infection in vitro, but the correlation between gene expression and kinetics of FIPV infection warrants further examination.